Implementation Of Self Muhasabah In The Islamic Discipline Of Medical Science (IDIK) At MPPD FK Umi - Nur Rahma M; Shulhana Mokhtar; Irmayanti Haidir Bima (Jurnal EduHealth, 2024)
A Muslim doctor has obligation to study well matters related to religion and the medical profession in which they are involved. Islamic Discipline of Science Medicine (IDIK) is one part of the integrated medical professional study program parts of the clinic. One of the programs from IDIK is do muhasabah daily . In method muhasabah daily ( assessment self ), student given containing form​ statements related the concept of worship and morals daily as well as interaction with Koran and Hadith. Muhasabah can be interpreted as self-reflection , pondering here is someone's attempt to make a change, namely: introspection self/be aware of something that has happened they do in their lives, so someone is capable of making improvements, and maximum improvement. Method study This nature qualitative with take background Faculty Indonesian Muslim University Medicine as location study . As for the results study show that activity muhasabah self has show positive results​ in the process of suing knowledge and doing activity daily as a student medical education profession. .